Fungsi Sistem Indera Manusia Perspektif Sains Terintegrasi Al-Qur’an dan Hadits - Siregar, Ida Yustika; Tanjung, Indayana Febriani; Maysarah, Siti (Letiges, 2021)
Human basically only know a science only from experts, without realizing the source of that knowledge. Science is the application of the Qur’an and Hadith is the source of knowledge. This study determine the integration of the functions of the sensory system according to the integrated scientific view of the Qur'an and hadith. The method used in this study is a qualitative method with the producing descriptive data in the words obtained when looking for references from literature sources with a literature review approach (Library Research). The results of this study indicate that the function of the human sensory system according to science is only in the essence of hearing, seeing, smelling, feeling and touching. In science the human senses function as producers of perception and even as facilities for developing knowledge about something. Meanwhile, according to the Qur'an and hadith, the function of the human sensory system is as a facility for increasing the faith and piety of a servant to Allah SWT. Based on science, the Qur'an and hadith both function the human senses as a complementary facilities in developing knowledge so that a person further increases the essence of Allah presence in carrying out sensory functions.